PMDFI: Predicting miRNA–Disease Associations Based on High-Order Feature Interaction - Tang, Mingyan; Liu, Chenzhe; Liu, Dayun; Liu, Junyi; Liu, Jiaqi; Deng, Lei (Frontiers in Genetics, 2021)
MicroRNAs (miRNAs) are non-coding RNA molecules that make a significant contribution to diverse biological processes, and their mutations and dysregulations are closely related to the occurrence, development and treatment of human diseases. Therefore, identification of potential miRNA-disease associations contributes to elucidating the pathogenesis of tumorigenesis and seeking the effective treatment method for diseases. Due to the expensive cost of traditional biological experiments of determining associations between miRNAs and diseases, increasing numbers of effective computational models are being used to compensate for this limitation. In this study, we propose a novel computational method, named PMDFI, which is an ensemble learning method to predict potential miRNA-disease associations based on high-order feature interactions. We initially use a stacked autoencoder to extract meaningful high-order features from the original similarity matrix, and then perform feature interactive learning, and finally utilize an integrated model composed of multiple RF and logistic regression to make comprehensive predictions. The experimental results illustrate that PMDFI achieves excellent performance in predicting potential miRNA-disease associations, with the average AUC value of 0.9404 and 0.9415 in five-fold and ten-fold cross-validation, respectively.